Peningkatan Kemampuan Membaca Al-Quran Pada Mata Pelajaran PAI dan Budi Pekerti Aspek Al-Qur'an Hadis untuk Siswa Kelas X TKJ 4 di SMKN 1 Badegan Ponorogo - Anis Wahyu Triana (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
This study aims to determine whether there is an increase in the ability to read the Koran in class X TKJ 4 at SMKN 1 Badegan Ponorogo after using the reading-aloud method. This research is classroom action research, and the data collection technique in this study is by observation and student ability tests. The results showed that: (1) the teacher's activity qualifications in cycle I was categorized as "good," with a score of 82.14%, and in cycle II, it increased to "very good" with an average score of 94.64%. As for the qualifications of student activities in the process I, it still needs to be better or more optimal because it has only reached 70.10%. In cycle II, student activity has increased to be good, with an average value of 84.56%. (2) The application of the reading-aloud method can improve the ability to read the Koran. This is evidenced by an increase in the completeness of student learning outcomes. Namely, in the first cycle, the average value is 70.10, and in the second cycle, it increases to 85.05%.